Low–memory video compression architecture using strip–based processing for implementation in wireless multimedia sensor networks. (23rd January 2012) - Chew, Li Wern; Chia, Wai Chong; Ang, Li–Minn; Seng, Kah Phooi
This paper presents a very low–memory video compression architecture for implementation in a wireless multimedia sensor network. The approach employs a strip–based processing technique where a group of image sequences is partitioned into strips, and each strip is encoded separately. A new one–dimensional, memory–addressing method is proposed to store the wavelet coefficients at predetermined locations in the strip buffer for ease of coding. To further reduce the memory requirements, the video–coding scheme uses a modified set–partitioning in hierarchical trees algorithm to give a high compression performance. The proposed work is implemented using a soft–core microprocessor–based approach. Simulation tests conducted have verified that even though the proposed video compression architecture using strip–based processing requires a much less complex hardware implementation and its efficient memory organisation uses a lesser amount of embedded memory for processing and buffering, it can still achieve a very good compression performance.